# Convergence of $\sum\limits_{n=1}^{\infty}(-1)^n\frac{n+2}{n^2+n+1}$

## Answer

\[\lim_{n \rightarrow \infty}\frac{\frac{n+2}{n^2+n+1}}{\frac{1}{n}}=1,\]

and hence by the Limit Comparision Test

\[\sum_{n=1}^{\infty}\frac{n+2}{n^2+n+1}\]

is divergent. Also since

\[\lim_{n\rightarrow}\frac{n+2}{n^2+n+1}=0,\]

by the Alternating Series Test

\[\sum_{n=1}^{\infty}(-1)^n\frac{n+2}{n^2+n+1}\]

converges conditionally but not absolutely.

Savionf

553

The answer is accepted.

Join Matchmaticians Affiliate Marketing
Program to earn up to a 50% commission on every question that your affiliated users ask or answer.

- answered
- 1740 views
- $2.00

### Related Questions

- Explain what the problem means in laymens terms.
- Optimization Quick Problem
- Epsilon delta 2
- Mechanical principle help (maths)
- Calculus / imaginary numbers and S^2
- Show that the MLE for $\sum_{i=1}^{n}\left(\ln{2x_i} - 2\ln{\lambda} - \left(\frac{x_i}{\lambda}\right)^2\right)$ is $\hat{\lambda} = \sqrt{\sum_{i=1}^{n}\frac{x_i^2}{n}}$.
- Calculus - stationary points, Taylor's series, double integrals..
- Uniform convergence of functions